El discurso del Estado chileno durante el régimen de Excepción: Dictadura de Pinochet y el 18 de octubre de Piñera - Ubilla, Mauricio (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
This article analyzes the role of the media in the development of a discourse that legitimizes state violence. Starting with the Pinochet dictatorship and Piñera's October 18 as similar historical moments, we are presented with violence in its discursive form and the role of the media as entities that justify the state of Emergency through the use of the word and the construction of an imaginary that seeks to annul conflicts and popular expression, avoiding the possibility of a communication that contributes to the construction of a pluralist democracy.
Keywords: dictatorship; mass media; Chilean 2019 riots; states of emergency